Victor Robert Simpson. (1st December 2018) - Lawson, Becki; Molenaar, Fieke; Duff, Paul
Abstract : A founder of wildlife disease surveillance in Great Britain and passionate advocate for evidence‐based conservation: the impact of his work studying the diseases of wildlife was immense.